Cerebrospinal fluid total protein cannot reliably distinguish true subarachnoid haemorrhage from other causes of raised cerebrospinal fluid net bilirubin and net oxyhaemoglobin absorbances. (November 2014) - Birch, Katherine; Burrows, Gillian; Cruickshank, Anne; Egner, William; Holbrook, Ian; Lewis, Emma; McNeilly, Jane; Patel, Dina; Worthington, Viki
Background: In cerebrospinal fluid (CSF) spectrophotometry, if the net bilirubin absorbance (NBA) and net oxyhaemoglobin absorbance (NOA) are both raised with a visible oxyhaemoglobin peak, the revised national guidelines for analysis of CSF bilirubin advise interpreting the results as 'Consistent with subarachnoid haemorrhage (SAH)' regardless of the CSF total protein concentration of the specimen. We wanted to study the range of CSF total protein concentrations found in confirmed SAH to establish if the CSF total protein value can give further guidance on the likelihood of SAH. Methods: Consecutive cases from five different hospital sites were included if the CSF NBA was greater than 0.007 AU and the NOA was greater than 0.02 AU with a visible oxyhaemoglobin peak. For the cases identified, the laboratory information management system and patient records were interrogated to identify the total protein concentration of the CSF specimen and whether SAH had ultimately been confirmed or excluded by other methods and supporting evidence. Results: Results from 132 patients were included. The CSF total protein range in confirmed SAH was 0.23–3.08 g/L with a median concentration of 0.7 g/L (n = 51). In the SAH excluded group, the CSF total protein range was 0.43–29 g/L with a median concentration of 1.9 g/L (n = 81). Conclusions: Although confirmed SAH was not associated with the very highest concentrations of CSF total protein, a definite CSF protein cut-off concentration above which SAH could reliably be excluded cannot be recommended.